A prospective investigation of neurodevelopmental risk factors for adult antisocial behavior combining official arrest records and self-reports. (September 2015) - Paradis, Angela D.; Fitzmaurice, Garrett M.; Koenen, Karestan C.; Buka, Stephen L.
Abstract: Neurodevelopmental deficits are postulated to play an important role in the etiology of persistent antisocial behavior (ASB). Yet it remains uncertain as to which particular deficits are most closely associated with ASB. We seek to advance this understanding using prospectively collected data from a birth cohort in which multiple indices of neurodevelopmental functioning and ASB were assessed. Participants ( n  = 2776) were members of the Providence, Rhode Island cohort of the Collaborative Perinatal Project. Information on demographic and neurodevelopmental variables was collected from pregnancy through age 7. When all offspring had reached 33 years of age an adult criminal record check was conducted. A subset of subjects also self-reported on their engagement in serious ASB. Bivariate logistic regression was used to examine the relationship between each neurodevelopmental factor and adult ASB and test whether associations varied depending on how ASB was ascertained. After controlling for background and contextual characteristics, maternal smoking during pregnancy, lower childhood verbal and performance IQ, and age 7 aggressive/impulsive behavior all significantly increased the odds of adult ASB. Associations were not modified by sex and did not depend on how ASB was assessed. However, while both males and Black participants were more likely to engage in ASB than their respective female and White counterparts, relationships were significantly stronger for official records than for self-reports. Results point to a particular subset of early neurodevelopmental risks for antisocial outcomes in adulthood. Findings also suggest that prior contradictory results are not due to the use of official records versus self-reported outcomes. Highlights: Results point to a subset of early neurodevelopmental risks for adult ASB. Factors included maternal smoking during pregnancy, lower childhood verbal and performance IQ, and aggressive/impulsive behavior. These associations were not modified by sex. Nor did they depend on how ASB was assessed (arrest records vs. self-report).